Implementing AES-RSA Hybrid Encryption to Enhance the Security of Salary Slip Distribution Information System - Abdullah, Riska Kurniyanto; Azhar, Nur Fajri; Mujahidin, Syamsul; Hoan, Richard Owen (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2025)
This study aims to enhance security and efficiency in the digital distribution of salary slips within the XYZ Higher Education environment. The proposed method combines hybrid encryption using the Advanced Encryption Standard (AES-128) and Rivest–Shamir–Adleman (RSA) algorithms, as well as integrates Time-Based One-Time Password (TOTP) for two-factor authentication. This approach ensures the confidentiality of sensitive data while minimizing the potential for data leakage or unauthorized access to employee salary information. In its implementation, the system is designed using the Laravel framework and the Scrum software development methodology, enabling an iterative, measurable, and easily adaptable development process. Testing results indicate that the system can distribute salary slips with an average data encryption time of 0.15 milliseconds per slip (using AES-128), and an average AES key decryption time with RSA of 5 milliseconds per operation over 100 test iterations. Furthermore, when two-factor authentication (TOTP) was applied, the rate of unauthorized access attempts dropped to 0% across 50 brute force attack simulation attempts. Thus, the hybrid encryption approach is proven effective in maintaining data integrity, and the integration of TOTP enhances user authentication security. These quantitative findings establish the system as a more measurable reference model for other institutions seeking to manage sensitive data securely, efficiently, and reliably.Penelitian ini bertujuan untuk meningkatkan keamanan dan efisiensi dalam pendistribusian slip gaji secara digital. Metode yang diusulkan yaitu memadukan enkripsi hibrida menggunakan algoritma (Advanced Encryption Standard) AES-128 dan (Rivest–Shamir–Adleman) RSA, serta mengintegrasikan Time-Based One-Time Password (TOTP) sebagai autentikasi dua faktor. Pendekatan ini memastikan kerahasiaan data sensitif, sekaligus meminimalkan potensi kebocoran atau akses tidak sah terhadap informasi gaji karyawan. Dalam implementasinya, sistem dirancang menggunakan kerangka kerja Laravel dan metodologi pengembangan perangkat lunak Scrum, sehingga memungkinkan proses pengembangan yang iteratif, terukur, dan mudah diadaptasi. Hasil pengujian menunjukkan bahwa sistem dapat mendistribusikan slip gaji dengan rata-rata waktu enkripsi data sebesar 0,15 milidetik per slip (menggunakan AES-128) dan waktu dekripsi kunci AES menggunakan RSA rata-rata 5 milidetik per operasi, pada skenario 100 percobaan. Selain itu, saat pengujian autentikasi dua faktor (TOTP) diterapkan, tingkat kegagalan akses tidak sah menurun hingga 0% pada 50 percobaan simulasi serangan bruteforce. Dengan demikian, enkripsi hibrida terbukti efektif dalam menjaga integritas data, dan integrasi TOTP meningkatkan tingkat keamanan autentikasi pengguna. Hasil kuantitatif ini dapat dijadikan sebagai model acuan yang lebih terukur bagi institusi lain yang ingin mengelola data sensitif secara aman, dan andal.